Vitamin-mineral correction of athletes' food ration - Semenova, N. V.; Lyapin, V. A.; Vasilevskaya, E. S.; Gotvald, A. R.; Elokhova, Y. A. (The Russian Journal of Physical Education and Sport, 2017)
Annotation. The main part of a sportsman`s balanced nutrition is getting necessary amount of vitamins and minerals. For a normal energetic balance a sportsman`s organism needs these things. They are the main components in the process of metabolism, in energy production process, in tissues development and growth. Lack of vitamins and minerals in an organism causes decrease of sports results and is harmful for health. Materials. The article is about the question of athletes` food ration vitamin-mineral correction. Research methods: scientific literature analysis and summarizing, description, comparative analysis. Results. In this literature review we analyze the most effective and widely used among sportsmen vitamin-mineral complexes. For power and speed trainings, as vitamin-mineral support of food ration, will suit polyvitamins "Vitrum Performance", "Undevit" (2 pills a day). They provide a daily rate of almost all vitamins. Although "Undevit" doesn`t contain many other useful substances, it is cost-effective in comparison with "Vitrum Performance". As a result of the content analysis of vitamin-mineral complexes in this literature review it was stated that for power and speed trainings as vitamin-mineral support of sportsmen food ration the most suitable polyvitamins are the following: "Vitrum Performance"and "Undevit". Conclusion. For power and speed trainings best of all will suit polyvitamins "Vitrum Performance", "Undevit". 2 pills of these preparations a day will provide a daily rate of almost all vitamins.